2014
DOI: 10.1902/jop.2013.130388
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Visfatin Concentrations in Patients With Chronic Periodontitis

Abstract: These results indicate that there is a relationship between salivary visfatin and CP; however, further studies are needed to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
7
27
0
1
Order By: Relevance
“…Mohamed et al reported a positive correlation between PD and GCF visfatin levels (34). Visfatin levels were also increased in the saliva following periodontal inflammation (35,36). These findings support our results that visfatin levels correlated positively with the severity of periodontitis.…”
Section: Discussionsupporting
confidence: 91%
“…Mohamed et al reported a positive correlation between PD and GCF visfatin levels (34). Visfatin levels were also increased in the saliva following periodontal inflammation (35,36). These findings support our results that visfatin levels correlated positively with the severity of periodontitis.…”
Section: Discussionsupporting
confidence: 91%
“…Tabari et al [17] reported that the rise in the visfatin levels was associated with CAL, but not with the other periodontal parameters. However, this finding was limited to the patients with periodontitis.…”
Section: Discussionmentioning
confidence: 98%
“…In their study with 50 healthy individuals, Mamali et al [32] reported that visfatin is an adipokine which can be identified and measured in the saliva. Tabari et al [17] evaluated the salivary visfatin levels in healthy individuals and in patients with periodontal disease together with the clinical periodontal parameters. They also concluded that visfatin levels can be measured in saliva and the levels are higher in chronic periodontitis compared to those of the healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient was classified as having hyposalivation if the saliva quantity was below 5 mL at end of 20-minute period. 3 Periodontal examination was done by a single examiner expert in periodontia to eliminate inter-examiner variability. Periodontal examination was conducted with all aseptic measures.…”
Section: Inclusion and Exclusionmentioning
confidence: 99%